GENERAL RESEARCH METHODS FOR POSITIONING STRATEGIES OF LEADING UNIVERSITIES IN WESTERN EUROPE - Hyrka, Iryna (Mountain School of Ukrainian Carpaty, 2019)
The article nalyzes the general methods for researching positioning strategies of leading universities in Western Europe. The main methods of scientific research revealed a method for studying the concepts and content of positioning of higher education institutions of leading universities in Western Europe; the relationship of educational and social services; communications; pricing. According to the author, the positioning strategy has an inter-scientific character, a constant process of self-development, self-regulation and self-healing of university positioning strategies, taking into account scientific and technological progress. Based on the analysis of scientific literature, the author defines methodological approaches to the analysis of positioning strategies of leading universities in Western Europe, namely: general science, which includes systemic, synergetic, strategic, social-marketing, critically complex; specifically scientific - system-comparative, system-strategic, system-methodological, system-methodological, system-didactic, system-component analysis, system-integrable, system-internal communicative, system-communicative, system-parametric, system-perspective). She also identified signs of positioning strategies of leading universities in Western Europe and trends in the further development of positioning strategies in the context of updating higher education in Ukraine. During the writing of the article, the researcher relied on the selected monographic and selective methods, as well as the method of the main array of positioning strategies of leading Western European universities for processing the analyzed literature at different stages. The author analyzed the sites of Times Higher Education (THE), QS World University Rankings; The Academic Ranking of World Universities (ARWU) of international university ratings, where the data were selected, with which the leading universities were compared, namely: academic reputation index; number of total students; number of international students; general citation of scientific publications; average annual number of scientific articles per member of the faculty.